Peptide with Dual Roles in Immune and Metabolic Regulation: Liver-Expressed Antimicrobial Peptide-2 (LEAP-2) - Yitong Li; Ying Liu; Meng Gou (Molecules)
Liver-expressed antimicrobial peptide 2 (LEAP-2) was originally discovered as an antimicrobial peptide that plays a vital role in the host innate immune system of various vertebrates. Recent research discovered LEAP-2 as an endogenous antagonist and inverse agonist of the GHSR1a receptor. By acting as a competitive antagonist to ghrelin, LEAP-2 influences energy balance and metabolic processes via the ghrelin–GHSR1a signaling pathway. LEAP-2 alone or the LEAP-2/ghrelin molar ratio showed potential as therapeutic targets for obesity, diabetes, and metabolic disorders. This review explores the recent advances of LEAP-2 in immune modulation and energy regulation, highlighting its potential in treating the above diseases.